Transumbilical single-site laparoscopic treatment of primary splenic cyst in child: a rare case report and review of literature - Kong, Meng; Chen, Shuai; Bai, Yuexia; Yan, Yuxi; Yi, Minggang; Wang, Meiyun; Liu, Hongzhen; Jia, Jinhua; Liu, Chuanyang; Zhang, Shisong (Frontiers in Pediatrics, 2024)
Background Splenic cysts are relatively rare benign tumors that are asymptomatic in most patients and are usually discovered incidentally by imaging. In our case, we report a splenic cyst in a child who underwent laparoscopic partial splenectomy. Case description A 13-year-old boy was admitted to the hospital after an incidental finding of a splenic cyst on an abdominal ultrasound conducted 4 days prior. He was asymptomatic before admission. Upon admission, abdominal ultrasound and CT revealed a cystic lesion in the spleen, highly suspicious for a splenic cyst. Then, we used transumbilical single-site laparoscopic exploration and found a cyst measuring approximately 12 cm × 11 cm × 10 cm at the upper pole of the spleen, so we performed a partial splenectomy and diagnosed a primary epithelioid splenic cyst via postoperative pathology. Conclusions Splenic cysts in children are very rare and can be treated conservatively in asymptomatic patients with a diameter of less than 5 cm, while surgery is required in symptomatic patients or those with a diameter greater than or equal to 5 cm. Transumbilical single-site laparoscopic partial splenectomy is a minimally invasive and effective treatment, especially for children.